PERLINDUNGAN HUKUM HAK PEKERJA OUTSOURCING PASCA PUTUSAN MAHKAMAH KONSTITUSI - Syarifa Mahila (Jurnal LEX SPECIALIS, 2012)
Abstract Outsourcing in Indonesia's labor law is defined as the contracted work and the provision of labor law regulation outsourcing in Indonesia under the Employment Act Ps. 64, 65, 66 and Kepmenakertrans. Kep 101/Men/VI/2004 2004. In its development, because they do not provide assurance work, trade unions / labor unions filed a resistance to the legalization of outsourcing and unspecified time employment agreement system by putting forward a judicial (judicial review) to the Constitutional Court. In the legal considerations, the Court offered two models pelaksananaan outsourcing are:The first model, outsourcing is done by applying an unspecified time employment agreement in writing.The second model, applying the principle of the transfer of protective measures for workers / laborers (Transfer of Undertaking Protection of Employment or Tupe).Court Decision on Outsourcing expected to anticipate the irregularities that employ workers with unspecified time employment agreement in writing continuously in order to avoid compliance with labor rights. Key Note : Outsourcing, Workers' rights